Status Hukum dan Hak Waris Bagi Anak Angkat yang Tidak Dimohonkan dengan Penetapan Pengadilan - Ida Ayu Kade Irsyanti Nadya Saraswati (Fakultas Hukum, Universitas Warmadewa, 2022)
The purpose of a marriage is to form a family and continue offspring. But not all familes are lucky to have a child. One way to overcome this is by adopting a child. Adoption of a child can be carried out based on national law or customary law. Adoption of children based on customs in Government Regulation Number 54 of 2007 is not required to obtain a court order. This will cause problems relaed to inheritance rights for adopted children who are not requested for a court order. On the one side, this provides legal certainty for customary lawbecause is is recognized by national law. But on the other side wthout wrtitten evidence, if there is a dispute over inheritance rights in court, the position of the adopted child is not strong enough if it does not have written evidence.